Jud Ashman for Gaithersburg Mayor - Dasgupta, Sunil; Ashman, Jud (I Hate Politics Podcast, 2024)
The City of Gaithersburg in Montgomery County, MD, is holding elections November 4. Two candidates are running for mayor: incumbent Jud Ashman and challenger Tiffany Kelly. In accompanying double-header episodes, Sunil Dasgupta talks with Ashman about rent stabilization. votejud.com Music By Adam Bobrow.
Keywords: I Hate Politics